2010
DOI: 10.1074/mcp.m900183-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Nanoproteomics for Protein Complexes (QNanoPX) Related to Estrogen Transcriptional Action

Abstract: We developed an integrated proteomics approach using a chemically functionalized gold nanoparticle (AuNP) as a novel probe for affinity purification to analyze a large protein complex in vivo. We then applied this approach to globally map the transcriptional activation complex of the estrogen response element (ERE). This approach was designated as quantitative nanoproteomics for protein complexes (QNanoPX). In this approach, the positive AuNP-ERE probes were functionalized with polyethylene glycol (PEG), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 62 publications
1
40
0
Order By: Relevance
“…It is worth mentioning that Arp2/3 and myosin 1c have been described to have a role with ␤-actin not only in regulating RNA polymerase II activity (35,48,49) but also in long range chromatin interactions involving hormoneresponsive genes and mediated by ER␣ (9). A recent study identified, by quantitative nanoproteomics (QNanoPX), several ERE-binding proteins from MCF-7 cell nuclei, including most of the ER␣ interactors reported in Table II (50). In vitro binding to ERE of a significant number of these proteins, including ER␣ itself, was found to be increased by estrogen treatment of the cells, suggesting that they might belong to multiprotein complexes also comprising the receptor.…”
Section: Fig 2 Tap-er␣ Protein Complex Purificationmentioning
confidence: 99%
“…It is worth mentioning that Arp2/3 and myosin 1c have been described to have a role with ␤-actin not only in regulating RNA polymerase II activity (35,48,49) but also in long range chromatin interactions involving hormoneresponsive genes and mediated by ER␣ (9). A recent study identified, by quantitative nanoproteomics (QNanoPX), several ERE-binding proteins from MCF-7 cell nuclei, including most of the ER␣ interactors reported in Table II (50). In vitro binding to ERE of a significant number of these proteins, including ER␣ itself, was found to be increased by estrogen treatment of the cells, suggesting that they might belong to multiprotein complexes also comprising the receptor.…”
Section: Fig 2 Tap-er␣ Protein Complex Purificationmentioning
confidence: 99%
“…5 Since the band intensities for this nonspecifically captured α-thrombin were so low, it can be concluded that the nonspecific capture of α-thrombin in the absence of the affinity tag conjugation was negligible.…”
Section: Resultsmentioning
confidence: 98%
“…Gold nanorods were functionalized with thiol-PEG (MW 5000) to avoid agglomeration and decrease nonspecific binding. 5,2731 …”
Section: Resultsmentioning
confidence: 99%
“…transcription associated with the proliferative response (35,36). We explored the possibility that estrogens can alter MCF7 cellular sensitivity to CRH by characterizing the effects of estrogens on CRH potential to induce kinase phosphorylation.…”
Section: Estrogens Alter Crh-r1 Splice Variant Expression and Crh Sigmentioning
confidence: 99%